Green operation barriers of Malaysia green operators - Yusof, Zeenat Begam; Jamaludin, Mariam (Association of Malaysian Environment-Behaviour Researchers (AMER); ABRAmalaysia, 2018)
Recently there has been a tremendous effort in greening the tourism industry due to its negative environmental impacts. The efforts of greening the green lodging industry in Malaysia is growing slowly due to the several barriers. The objective of this study is to determine the barriers that slowing the green hotels and resorts operation in Malaysia. This study employed qualitative method using interview technique. Five case studies were chosen and the environmental managers are interviewed. The findings identified 12 barriers. The barriers are categorized under significant, less significant and non- significant barriers that affecting lodging green operation in Peninsular Malaysia.